PENGARUH KUALITAS PRODUK DAN LOKASI TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING ( Studi Kasus Pada Pelanggan Mertojoyo Cake Semarang ) - Putri, Dea Irana; Hidayat, Wahyu; Dewi, Reni Shinta (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to determine the effects of variable product quality, location and satisfaction through customer loyalty at Mertojoyo Cake Semarang. There were 100 respondents as the sample of this research, who were the customer of Mertojoyo Cake Semarang. The sampling technique used was purposive sampling. Whereas, the method of analysis used in this research was path analysis. From the analysis of the data is known that from the product quality category, 9 per cent stated it was quite good, 57 percent stated good, and 34 percent stated very good. From location category, 42 percent stated it was not on a good location, 53 percent stated quite good, and 5 percent stated it was on a good location. From satisfaction category, 39 percent stated quite high, 56 percent stated high, and 5 percent stated very high. From customer loyalty category, 31 percent stated it was quite high, 60 percent stated high and 9 percent stated very high. Product quality variables affect the customer loyalty at 48.1 percent. Partially, location variable does not affect customer loyalty, but simultaneously, it does. The determination coefficient is 0.5 percent. Satisfaction variables affect the customer loyalty at 14.3 percent. Taken together, product quality, location and satisfaction affect the customer loyalty at 56.1 percent. This means the better the product quality, location and satisfaction of customers, the better the customer loyalty.